Public policy challenges and perspectives in reducing intentional lethal violent crimes in Northern Brazil (Research, Society and Development, 2020)
This study aimed to analyze violent criminality in Northern Brazil, as well as to understand why, the Southeast region, specially the state of São Paulo, has the lowest crime rate. To achieve the objectives, a descriptive and bibliographic research was carried out, in which statistical data from several databases were used, among which stands out the Brazilian Institute of Geography and Statistics, Atlas of Violence, Brazilian Forum on Public Security. The results indicate that the Northern region of Brazil is currently one of the most violent regions. This information reveal that the strengthening of operators and managers of public security agencies, quality education and employment and income can contribute to the reduction of crime.